Interactive learning using augmented reality - Nurliana, Ramli (2012)
A learning interactive project is developed to provide a platform for user to interact more in the learning environment compared to conventional learning environment. This project purpose a conceptual model for exploring the prospect of a new form of Virtual Reality (VR)application called Augmented Reality(AR)technology in education domain. AR sets itself apart from VR by allowing integration of 3D virtual objects into real environment in real time thus allowing student to relate with their physical environment and also making learning more interesting.AR learning offers interaction such as screen touching,device flipping,device rotating,etc. To let users experience a new technology learning style. Overall project has less difference in term of materials of learning,changes will be made in term of performances and how represent the materials in AR such as adding multimedia elements and sound.This project will benefits teachers as well as students. It provides the teachers teaching aids and transforms the learning session to be more interactive,attractive and effective.It will assist students in building their creative thinking, improving their comprehension, and changing the paradigm of learning.